(untitled) (International Journal of Engineering and Computer Science, 2015)
The structural aspects of a long blade in a an up wind, horizontal-axis wind turbine were hybrid composite structure using glass and carbon fiber plies was created yielding a light-weight design with a low tip deflection. The results confirmed the design to have acceptable performance with regard to tip deflection, maximum and minimum strains, and a critical load. Detailed descriptions of the structural components and ply layups are presented along with resulting maximum and minimum strains and deflections. In addition, optimization techniques were introduced to provide insight for future studies with the blade a detailed review of current state of art for wind turbine blade design is presented. A design different airfoil cross section (‘I’,‘C’, Double ‘C’).and Structural analysis, FatigueCharacterics of Wind Turbine Blade.